Evaluation of inhibitory activity, purification and X-ray crystallography of Alpha-Amylase inhibitor from Phaseolus vulgaris cultivars of Uttarakhand, India - Singh,R. (2024)
Abstract The present work is based on analysis of inhibitory activity of alpha-amylase inhibitor in selected cultivars of Phaseolus vulgaris of Uttarakhand. Fifteen samples were assessed for inhibitory activity of alpha-amylase inhibitor. Significant variations were found in different cultivars. Crude extract of alpha-amylase inhibitor from sample PUR (Purola) have shown maximum inhibitory activity (70.2 ± 0.84). Crude extract of all the cultivars have shown considerable variations in inhibitory activity in the temperature ranging from 20ºC to 100ºC. Based on inhibitory activity and heat stability profile, the alpha amylase inhibitor was purified from PUR cultivar. The purified inhibitor was found to be stable even at 90ºC with an inhibitory activity of 97.20 ±0.09. The molecular weight of purified inhibitor on Native PAGE (Polyacrylamide gel electrophoresis) was found to be 31kd, consisting of two subunits of 17kd and 14kd on SDS-PAGE.